2015
DOI: 10.3390/molecules20058856
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles as Potential Antibacterial Agents

Abstract: Multi-drug resistance is a growing problem in the treatment of infectious diseases and the widespread use of broad-spectrum antibiotics has produced antibiotic resistance for many human bacterial pathogens. Advances in nanotechnology have opened new horizons in nanomedicine, allowing the synthesis of nanoparticles that can be assembled into complex architectures. Novel studies and technologies are devoted to understanding the mechanisms of disease for the design of new drugs, but unfortunately infectious disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
796
1
26

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,407 publications
(909 citation statements)
references
References 104 publications
19
796
1
26
Order By: Relevance
“…There are several antimicrobial mechanisms reported by researchers (Morones et al 2005;Kim et al 2007;Sanpui et al 2008;Rai et al 2009;Chudobova et al 2013). Overall, combinations of mechanisms include: cell membrane disruption, denaturation of ribosomes, enzymes and proteins inactivation, depletion of intracellular ATP levels, decrease DNA replication (Feng et al 2000;Li et al 2010;Chudobova et al 2013), formation of free radicals (hydroxyl and ROS), oxidative stress and inactivating the respiratory chain (Chudobova et al 2013;Zhang et al 2014;Franci et al 2015). This reveals that more studied are required to evaluate antibacterial mechanisms of AgNPs on bacterial pathogens in aquatics.…”
Section: Discussionmentioning
confidence: 99%
“…There are several antimicrobial mechanisms reported by researchers (Morones et al 2005;Kim et al 2007;Sanpui et al 2008;Rai et al 2009;Chudobova et al 2013). Overall, combinations of mechanisms include: cell membrane disruption, denaturation of ribosomes, enzymes and proteins inactivation, depletion of intracellular ATP levels, decrease DNA replication (Feng et al 2000;Li et al 2010;Chudobova et al 2013), formation of free radicals (hydroxyl and ROS), oxidative stress and inactivating the respiratory chain (Chudobova et al 2013;Zhang et al 2014;Franci et al 2015). This reveals that more studied are required to evaluate antibacterial mechanisms of AgNPs on bacterial pathogens in aquatics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is a great need of silver nanoparticles because of their antibacterial and anti-inflammatory properties 1,2 . Commercially, SNPs are synthesized by means of chemical methods using reducing agents such as sodium borohydride, hydrazine, N, N-dimethylformamide in the presence of stabilizers like triphenylphosphine, citrate, polyvinylpyrrolidone [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Then, the freshly grown bacterial culture was centrifuged and the supernatant was collected and filtered through sterile 0.22-µm filter to sterile flasks. Cell free supernatant was subjected to synthesis of AgNPs [9].…”
Section: Growth Of Bacillus Subtilismentioning
confidence: 99%
“…Several reports have successfully demonstrated that AgNPs have antimicrobial activity against a broad range of Gram-negative and Gram-positive including the pathogenic bacteria [9]. To determine the antibacterial effectiveness of AgNPs and consequences of their release into environment, studying the effect of AgNPs on biofilms is important because bacteria are often present in biofilm communities.…”
Section: Introductionmentioning
confidence: 99%